Pelatihan Aplikasi Pemasaran dan Penjualan Produk UMKM Berbasis Website : Training of Marketing and Sales Applications for UMKM Product Based Website - Sekreningsih Nita; Fatim Nugrahanti; Firman Primawan (Jurnal Suara Pengabdian 45, 2022)
The rapid development of information technology requires people tobe familiar with the internet. Utilization of marketing and sales applications is not only carried out by large companies, but can also be used by Micro, Small and Medium Enterprises (MSMEs). The community service team conducted observations and interviews with Brem Duta Rasa SMEs in Sumberejo, Kaliabu, Mejayan, Madiun Regency. The team found problems with promotion and sales, therefore it was necessary to provide asolution, namely by using awebsite-based marketing and sales application for MSME products. The activity method of the service team is to provide practical training using applications. The final result of the evaluation shows that 90% of the 10 users of MSME members have theoretical understanding, 95% of application introductions, 80% of practice running applications. In conclusion, all MSME members running the application quite well. Applications can be implemented continuously to increase revenue from Brem Duta Rasa MSME products